The epistemology of the value of aqidah akhlaq education in Biyanglala poetry book by Abdul Wachid B.S. (A semiotic study) - Metros Prihatin; Heru Kurniawan; Adi Purnomo (BAHASTRA, 2021)
The purpose of this paper is to analyze and describe the value of aqidah akhlaq education in Abdul Wachid B.S.â€™s poems especially in Biyanglala. The method used in this research was qualitative research method of library research where the data collection technique is carried out by studying the reading in the form of lecture notes, books, literature and regulations related to the problem under study. The object of research in this paper is the Biyanglala poetry book. To analyze and describe the value of aqidah akhlaq education in the poetry book, the writer uses Michael Riffaterre's semiotics. According to the results of the study, the writers found out that Biyanglala poetry book by Abdul Wachid B.S.â€™s contained the value of aqidah akhlaq education, namely in the poetry "Ketika Lima Puluh Tahun", "Hujan Pagi" and â€œStasiun Sebuah Pertemuanâ€. The poem "Ketika Lima Puluh Tahun" is a poetry model for the value of faith and the poem "Hujan Pagi" is a poetry model for moral values. The poem "Ketika Lima Puluh Tahun" gives a message of surrender or submission of the â€œIâ€ to God. How pure tawakal must be relied on to the Almighty and the All- and Oft-Forgiving, Allah SWT. The poem "Hujan Pagi" implies moral values such as responsibility, good prejudice and gratitude for the blessings and grace that Allah has given. The poem â€œStasiun Sebuah Pertemuanâ€ is a poem that contains monotheistic value about asma wa shifat. The Poem â€œSuaraâ€ contains a message to always be honest.